Sistem Informasi Penilaian Kinerja Pegawai Kejaksaan - Dwi Syaputri, Lucky; Effiyaldi , Effiyaldi (Jurnal Manajemen Sistem Informasi, 2023)
The management of employee performance appraisal at the Batanghari District Attorney's Office is still managed with Microsoft Excel so that problems occur, namely errors in processing employee assessment data such as inputting employee performance values, Making a final report on employee assessment based on criteria takes a long time and there can also be a miscap of employee final scores, and sometimes there are errors in the process of calculating employee assessments. The purpose of the study is to facilitate the search for data, especially for staffing and assessment data so as to reduce the occurrence of errors in data management and can provide fast and precise information according to their needs. The solution to the problems that occur by analyzing and designing an employee performance appraisal information system using prototype development methods and a unified model language system model using usecase diagrams, activity diagrams, and class diagrams. The results of system development can display job title data, echelon data, employee data, criteria data and assessment data and produce reports that can be printed according to their needs. Suggestions from the study can add features for ranking grades and perform assessment comparisons for all employees based on assessment criteria.